2019
DOI: 10.1111/ecc.13000
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for reducing emergency diagnoses of colon cancer in women and men: A data-linkage study on pre-diagnostic symptomatic presentations and benign diagnoses

Abstract: Objectives To identify opportunities for reducing emergency colon cancer diagnoses, we evaluated symptoms and benign diagnoses recorded before emergency presentations (EP). Methods Cohort of 5,745 colon cancers diagnosed in England 2005–2010, with individually linked cancer registry and primary care data for the 5‐year pre‐diagnostic period. Results Colon cancer was diagnosed following EP in 34% of women and 30% of men. Among emergency presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Six studies examined variation by tumour characteristics. As indicated by changes in primary care consultation rates in two studies, reported diagnostic windows were generally longer for proximal colon compared to distal colon or rectal cancer [17] , [33] . Increases in prescription rates for any newly-prescribed drug occurred earlier for proximal colon compared to distal colon or rectal cancer, [33] whereas increases in haemorrhoid prescription rates were earlier for rectal compared to colon cancers [10] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies examined variation by tumour characteristics. As indicated by changes in primary care consultation rates in two studies, reported diagnostic windows were generally longer for proximal colon compared to distal colon or rectal cancer [17] , [33] . Increases in prescription rates for any newly-prescribed drug occurred earlier for proximal colon compared to distal colon or rectal cancer, [33] whereas increases in haemorrhoid prescription rates were earlier for rectal compared to colon cancers [10] .…”
Section: Resultsmentioning
confidence: 99%
“…763 studies were initially identified, of which 28 were included in the final review ( Fig. 2 ) [10] , [11] , [12] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] . All but four of the selected studies were carried out in Denmark or the UK, while the four remaining studies were set in Germany, Sweden, Australia, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately a third of colorectal and lung cancer diagnoses in the USA have missed diagnostic opportunities despite ‘red flag’ symptoms (eg, rectal bleeding) 5 6. In England, one in five patients with colorectal cancer diagnosed after an emergency presentation had typical ‘alarm’ symptoms in the year leading up to their diagnosis, and 16%–22% had three or more consultations in primary care with relevant symptoms, suggesting potential opportunities for earlier diagnosis 7 8. This points to the importance of understanding what happens within the consultation to prevent patient harm resulting from missed or delayed diagnosis 9…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Renzi, Lyratzopoulos, Hamilton, and Rachet () examined emergency diagnosis of colon cancer in women and men. Women were at increased risk, due, it seemed, to less specific symptomology or more frequent attribution to a benign diagnosis.…”
mentioning
confidence: 99%